Penanaman Kemandirian Belajar Matematika Pada Anak Berkebutuhan Khusus Di Smp Al Firdaus (Studi Etnografi Anak Tunagrahita Ringan (Debil) dan Tunagrahita Sedang (Imbesil) Semester Genap Tahun 2015/2016) - Rovania, Hesti; , Rita P. Khotimah, S.Si., M.Sc (2016)
The purpose of this study to describe the barriers of learning and process inculcation independent learning mathematic in children mild mental retardation (debilitated) and severe mental retardation (imbecile) in SMP AL FIRDAUS. This study is based on the approach is qualitative descriptive. This type of research is etnografi. Technic collection of data through observation, interviews and documentation. The validity of data by triangulation of sources and techniques. Analysis of data through the stages of data reduction, data presentation, and conclusion. The results of this study indicate that barriers to learning mathematics for children mild mental retardation is easy to forget that making a shadow teacher must repeat the same material over and over again, have not been able to understand the contents of the reading and follow assignments at home. Barriers to learning mathematics for children with savere retardation mental being is difficult to communicate, it is difficult to remember numbers in mathematics, and difficulty in abstract thinking and complicated.Planting efforts independent learning of mathematics in children retardation mental are given exercises to do homework subjects of mathematics with the help of parents to observe, asked to learn math in a group with her friends so she learned to communicate and socialize with the surrounding environment, abandoned by teachers companion to sharpen a child's ability to follow the task by giving the message if it is completed or there is asked to solve problems then meet a teachers in a place that has been agreed upon, to the learning material of mathematics if easy and son tunagrahita able to do it yourself then shadow teacher just watched from the back of the class and implementing learning outing class which aims to train independence life in community by applying a mathematical science that has been given by the teacher.